A Sinorhizobium meliloti-specific N-acyl homoserine lactone quorum-sensing signal increases nodule numbers in Medicago truncatula independent of autoregulation - Veliz-Vallejos, Debora F.; van Noorden, Giel E.; Yuan, Mengqi; Mathesius, Ulrike (Frontiers in Plant Science, 2014)
N-acyl homoserine lactones (AHLs) act as quorum sensing signals that regulate cell-density dependent behaviors in many gram-negative bacteria, in particular those important for plant-microbe interactions. AHLs can also be recognized by plants, and this may influence their interactions with bacteria. Here we tested whether the exposure to AHLs affects the nodule-forming symbiosis between legume hosts and rhizobia. We treated roots of the model legume, Medicago truncatula, with a range of AHLs either from its specific symbiont, Sinorhizobium meliloti, or from the potential pathogens, Pseudomonas aeruginosa and Agrobacterium vitis. We found increased numbers of nodules formed on root systems treated with the S. meliloti-specific AHL, 3-oxo-C14-homoserine lactone, at a concentration of 1 μM, while the other AHLs did not result in significant changes to nodule numbers. We did not find any evidence for altered nodule invasion by the rhizobia. Quantification of flavonoids that could act as nod gene inducers in S. meliloti did not show any correlation with increased nodule numbers. The effects of AHLs were specific for an increase in nodule numbers, but not lateral root numbers or root length. Increased nodule numbers following 3-oxo-C14-homoserine lactone treatment were under control of autoregulation of nodulation and were still observed in the autoregulation mutant, sunn4 (super numeric nodules4). However, increases in nodule numbers by 3-oxo-C14-homoserine lactone were not found in the ethylene-insensitive sickle mutant. A comparison between M. truncatula with M. sativa (alfalfa) and Trifolium repens (white clover) showed that the observed effects of AHLs on nodule numbers were specific to M. truncatula, despite M. sativa nodulating with the same symbiont. We conclude that plant perception of the S. meliloti-specific 3-oxo-C14-homoserine lactone influences nodule numbers in M. truncatula via an ethylene-dependent, but autoregulation-independent mechanism.